Neural Mechanisms Underlying the Rewarding and Therapeutic Effects of Ketamine as a Treatment for Alcohol Use Disorder - Strong, Caroline E.; Kabbaj, Mohamed (Frontiers in Behavioral Neuroscience, 2020)
Alcohol use disorder (AUD) is the most prevalent substance use disorder and causes significant global burden. Relapse rates remain incredibly high after decades of attempting to develop novel treatment options that have failed to produce increased rates of sobriety. Ketamine has emerged as a potential treatment for AUD following its success as a therapeutic agent for depression, demonstrated by several preclinical studies showing that acute administration reduced alcohol intake in rodents. As such, ketamine’s therapeutic effects for AUD are now being investigated in clinical trials with the hope of it being efficacious in prolonging sobriety from alcohol in humans (ClinicalTrials.gov, Identifier: NCT01558063). Importantly, ketamine’s antidepressant effects only last for about 1-week and because AUD is a lifelong disorder, repeated treatment regimens would be necessary to maintain sobriety. This raises questions regarding its safety for AUD treatment since ketamine itself has the potential for addiction. Therefore, this review aims to summarize the neuroadaptations related to alcohol’s addictive properties as well as ketamine’s therapeutic and addictive properties. To do this, the focus will be on reward-related brain regions such as the nucleus accumbens, dorsal striatum, prefrontal cortex, hippocampus, and ventral tegmental area to understand how acute versus chronic exposure will alter reward signaling over time. Additionally, evidence from these studies will be summarized in both male and female subjects. Accordingly, this review aims to address the safety of repeated ketamine infusions for the treatment of AUD. Although more work about the safety of ketamine to treat AUD is warranted, we hope this review sheds light on some answers about the safety of repeated ketamine infusions.